1982
DOI: 10.1139/v82-064
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic photochemistry: micelle solutions as media for photochemical cycloadditions of enones

Abstract: The possible application in synthesis of a micellar solution as a medium in the photocycloaddition of enones to alkenes has been examined. It is found that the micelles are useful in increasing the effective concentration of reactants, have some ability in directing reaction regiochemistry, and may reduce hydrogen atom transfer in intermediate biradicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 10 publications
2
34
0
Order By: Relevance
“…For example, photocycloaddition of 3-n-butylcyclopentanone in the presence of heptenyl acetate in organic solvents gives a single adduct B (Scheme 6). [204][205][206] Irradiation of these two compounds solubilized in a potassium decanoate micelle yields a mixture of two adducts A and B in which the A is the major product and consistent with the notion that a micellar interface helps orient the reactant molecules (Figure 8). A few years ago, our group demonstrated that alkenes photostable in the solid state dimerize within cucurbiturils.…”
supporting
confidence: 78%
“…For example, photocycloaddition of 3-n-butylcyclopentanone in the presence of heptenyl acetate in organic solvents gives a single adduct B (Scheme 6). [204][205][206] Irradiation of these two compounds solubilized in a potassium decanoate micelle yields a mixture of two adducts A and B in which the A is the major product and consistent with the notion that a micellar interface helps orient the reactant molecules (Figure 8). A few years ago, our group demonstrated that alkenes photostable in the solid state dimerize within cucurbiturils.…”
supporting
confidence: 78%
“…Given the low combined yield for compounds 17 and 18 , it is likely that other dimerization products were formed but could not be isolated in a pure form. [2 + 2] Photodimerization, in a head-to-head fashion, is common for cyclopentenones, 23 while the regioselectivity of the intermolecular head-to-head double bond addition of a monosubstituted olefin to an enone has less precedence. 9d , 23d , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Vinylogous thioesters (A3, Q ¼ S) have been used less frequently in [2 þ 2]photocycloaddition as compared to their oxygen and nitrogen analogues [83]. More recent applications can be found in the above-mentioned study with chiral allenes [79].…”
Section: -Hetero-2-cyclohexenonesmentioning
confidence: 99%